Study of the dielectric relaxation of poly(phenylpropyl acrylate) and poly(phenylpropyl methacrylate): effect of slight differences in chemical structure. Issue 12 (19th August 2015) - Ortiz‐Serna, Pilar; Sanchis, María J; Redondo‐Foj, Belén; Carsí, Marta; Díaz Calleja, Ricardo; Leiva, Angel; Gargallo, Ligia; Radić, Deodato
<x xml:space="preserve">Abstract</x> The effect of slight differences in the chemical structure of two structurally related polymers, namely poly(phenylpropyl acrylate) (P3Ph1PA) and poly(phenylpropyl methacrylate) (P3Ph1PM), on the molecular mobility was studied by means of differential scanning calorimetry and dielectric relaxation spectroscopy.<boxed-text content-type="graphic" id="pi4973-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>